Design and development of an autonomous glass cleaning robot - Ma, Jun (2014)
At present, there are more and more high-rise buildings in modern cities, whose curtain walls require constant cleaning. Glass cleaning is usually carried out with the help of a permanent gondola system hanging from the roof of the building. However, safety is the biggest concern to those human operators who work high above the ground. Therefore, glass cleaning and maintenance of high-rise buildings is becoming one of